2004
DOI: 10.1177/154405910408300209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dental Epithelial Progenitor Cells Derived from Cervical-loop Epithelium in a Rat Lower Incisor

Abstract: Dental epithelial progenitor cells differentiate into various cell types during development of tooth germs. To study this mechanism, we produced immortalized dental epithelial progenitor cells derived from the cervical-loop epithelium of a rat lower incisor. The expression patterns of cytokeratin 14, nerve growth factor receptor p75, amelogenin, Notch2, and alkaline phosphatase were examined by immunohistochemistry in both lower and higher cell densities. The patterns of each were compared in the dental epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 24 publications
4
63
0
Order By: Relevance
“…Occurrence of ALP mRNA detected by RT-PCR indicated the spontaneous mineralization ability of ABCs during culture. These results are in agreement with the previous reports which demonstrate that dental epithelial stem cells reside in the apical bud of mouse lower incisors and these cells produce IEE cells as transitamplifying progenitor cells which differentiate into ameloblasts (Harada et al, 1999;Kawano et al, 2004;Harada et al, 2004). In circumstances where adult stem cells survive and proliferate, they undergo the course during which the asymmetric cell division results in the production of one daughter cell remaining in the stem cell compartment and another undergoing further cell divisions and giving rise to differentiated cells (Harada et al, 1999;Morrison et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Occurrence of ALP mRNA detected by RT-PCR indicated the spontaneous mineralization ability of ABCs during culture. These results are in agreement with the previous reports which demonstrate that dental epithelial stem cells reside in the apical bud of mouse lower incisors and these cells produce IEE cells as transitamplifying progenitor cells which differentiate into ameloblasts (Harada et al, 1999;Kawano et al, 2004;Harada et al, 2004). In circumstances where adult stem cells survive and proliferate, they undergo the course during which the asymmetric cell division results in the production of one daughter cell remaining in the stem cell compartment and another undergoing further cell divisions and giving rise to differentiated cells (Harada et al, 1999;Morrison et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…In most mammalian developing molars, cervical loop derived Hertwig's epithelial root sheath (HERS) induces and conducts tooth root and periodontal tissue development after tooth crown formation (Hammarström et al, 1996;Luan, et al, 2006;ZeichnerDavid et al, 2003). In contrast, continuous growth throughout the lifetime can be observed in the murine incisor, rendering it a special tooth type (Smith et al, 1975;Harada et al, 1999;Harada et al, 2002;Kawano et al, 2004;Harada et al, 2004;Ohshima et al, 2005). The explanation for this speciality lies in the fact that the specific epithelial structure, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…The rodent incisor is a unique model for studying dental EpSC since, in contrast to human incisors or other vertebrates, this tooth grows throughout life. An EpSC niche, which is located in the apical part of the rodent incisor epithelium (cervical loop area), is responsible for a continuous enamel matrix production (Harada et al, 1999;Kawano et al, 2004;Mitsiadis et al, 1998Mitsiadis et al, , 2007Smith and Warshawsky, 1975). In this highly proliferative area, undifferentiated epithelial cells migrate toward the anterior part of the incisor and give rise to ameloblasts (Fig.…”
Section: Periodontal Ligament Stem Cells (Pdlsc)mentioning
confidence: 99%
“…It has been reported that the growth rate of dental epithelial progenitor cells derived from rat cervical loop, where enamel epithelium is maintained for the continuous growth of rodent incisors, was increased in the presence of FGF-10 at each dose of 10 to 100 ng/ml after 4 day culture based on formazan dye assay [7] and 10 ng/ml after 48 h culture based on the BrdU incorporation experiment [26]. In the ameloblastoma cell line, FGF-10 stimulated the growth of cells in the presence of FGF-10 at 10 or 100 ng/ml after 3 day culture using the same cell counting kit as that in our experiment [23].…”
Section: Discussionmentioning
confidence: 99%
“…Among these FGFs, the gene expression of FGF-9 and FGF-10 in dental epithelium is strongly involved in tooth development [3][4][5], and FGF-9 expression in the dental epithelium of mouse incisors regulates ameloblast differentiation [6]. Furthermore, FGF-9 or FGF-10 promotes in Human Amelobastoma Epithelial Cell Proliferation the cell proliferation of the dental epithelial progenitor cells established from rat incisors [7] and the dissociated epithelial cells detected in mouse molars [8]. There are few findings on the effect of these FGFs on dental epithelial cells, however, and no study has reported them in ameloblastoma cells.…”
Section: Introductionmentioning
confidence: 99%